PELATIHAN MENDRIBEL MEMBENTUK BINTANG MENINGKATKAN KELINCAHAN PADA SISWA SLTP DI KECAMATAN MENGWI BADUNG - Dei, Agustinus; Sandi, I Nengah; Womsiwor, Daniel (Sport and Fitness Journal; Volume 5, No.3, 2017, 2017)
Background: The agility is very important for a football player to achieve the desired achievement. It requires training that supports the agility of the biomotoric component. Objective: The purpose of this study was to investigate the effect and differentiation of the training of dribbling spheres to form stars with different doses of agility. Method: This study used pre-post group design, where the subjects of junior high school students on Mengwi Badung sub-district were 48 people divided into two groups then given different treatment. Group 1 was given a training on dribbling a star ball with a length of 25 meters as many as 10 reps 2 sets. Group 2 was given training on the same track as many as 5 reps 4 sets. Each group is trained 3 times per week for six weeks. The data obtained were analyzed using t-test formula at 5% significance level. Result: The value of t arithmetic in Groups 1 and Group 2 is greater than t table (respectively 11,679> 2,069 and 8,533> 2,069). The t value of the difference between Group 1 and Group 2 is smaller than t table (1.557 <2.013). Conclusion: It was concluded that there is an effect of the training of dribbling the ball on both groups against agility but no difference in effect Training dribble ball 10 reps 2 sets and 5 reps 4 sets against agility. Suggestion: It is advisable to provide varying training on both types of training to reduce the saturation in exercise.